Application of state space models to model unemployment rate data in Metropolitan Lima - Sikov, Anna (2020)
The dynamics of the unemployment rate over time reflects the performance of the labor market, one of the most important determinants of well-being in any economy. The unemployment rate is one of the main indicators used to analyze the prosperity and economic situation of a country, and also allows analyzing the economy from two perspectives: the first from the supply side and from the demand side. In this research we are going to analyze the dynamics of unemployment in Metropolitan Lima.For this purpose, we will use the data from the Permanent Employment Survey - EPE from 2002 to 2018 to calculate the monthly unemployment rates. We are interested in studying the development dynamics of the unemployment rate in Metropolitan Lima, and also in comparing the development dynamics ofthe said rate in different cones, men and women, and also the dynamics in different age groups. The main objective of our research is to study the dynamics of unemployment rates in different social groups to identify possible problems of inequality of opportunities in the same groups, and to explain the economic and social roots that generate this inequality. To estimate the monthly unemployment rates and their respective variances we use the Horvitz-Tompson estimator. To analyze the dynamics of the series we adjust the basic structure model, which is a special case of state space models.